Mortality Predictors in Spontaneous Intracerebral Hemorrhage: External Validation of the ICH Score in the Indonesian Surgical Population - Grady Christian; Trijoso Permono; Ziske Maritska (Sriwijaya Journal of Surgery, 2026)
Introduction: Spontaneous intracerebral hemorrhage (ICH) is a major contributor to stroke-related mortality and long-term disability, particularly in Indonesia, which faces the highest age-standardized stroke mortality rate in Southeast Asia. This study evaluates the predictive accuracy of the ICH Score for 30-day mortality among patients undergoing surgical intervention at a primary referral center in South Sumatra. Methods: This analytical observational study utilized a retrospective cohort design, analyzing 81 patients with spontaneous ICH who underwent surgical evacuation at Dr. Mohammad Hoesin Central General Hospital Palembang between July 2024 and June 2025. Demographic, clinical, and radiological parameters were evaluated. Accuracy was determined using Receiver Operating Characteristic (ROC) curve analysis to establish the Area Under the Curve (AUC), sensitivity, and specificity. Results: The cohort was predominantly male (56.8 percent) and aged under 80 years (86.4 percent). Significant predictors of 30-day mortality included age 80 years or older (p < 0.001, OR 26.84), lower Glasgow Coma Scale (GCS) scores (p = 0.012), and the presence of intraventricular hemorrhage (IVH) (p < 0.001, OR 15.24). ROC analysis demonstrated an AUC of 0.958 (95 percent CI 0.910–1.000). An optimal ICH Score cut-off of 3 or higher yielded a sensitivity of 86.2 percent and a specificity of 100 percent. Conclusion: The ICH Score serves as an exceptionally accurate prognostic tool in the Indonesian surgical population. An admission score of 3 or higher is a definitive predictor of mortality, facilitating risk stratification and informed clinical decision-making.